Speech-acts Strategies of Indonesian Television Talkshow Host: Indonesian Lawyer Club Weekly Program - Ani Rakhmawati; Intan Sulistyorini (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2021)
Becoming a successful television talk show presenter is an important effort to bring a program progressing smoothly to a successful ending. To accomplish this challenge, this article reports the result the analysis of one program namely the Indonesia Lawyers Club talk show hosted by Karni Ilyas. This paper aims to describe and explain: (1) the politeness strategies of the program host's, and (2) the expressive speech-act of the host in the Indonesia Lawyers Club talk show on television shows that air on TV One. The type of research is descriptive qualitative. Using purposive sampling, the data source was the episode of "Aduh, Suporter Bola". Content analysis was used as a technique. The results showed: (1) the politeness of the program host includes positive politeness strategies and negative politeness strategies; and (2) expressive speech act of the host include gratitude, criticism, condolences, expressing curiosity, expressing hope, regretting, expressing agreement, congratulating, suspecting, apologizing, and expressing concern. Karni Ilyas's politeness strategy in guiding the talk show was accepted satisfactorily in accordance with the context of multicultural Indonesian society.